POINTS OF VIEW, FRAMES, SCENARIOS… AND MODELS POINTS OF VIEW, FRAMES, SCENARIOS… AND MODELS - Vázquez Campos, Margarita (Analysis. Journal of Philosophical Research, 2024)
This paper explores the conceptual distinctions and interrelations between “point of view”, “frame”, “scenario”, and “model”. I introduce the concept of “model” as a bridge between a subject's point of view and the relational structure that constitutes the frame, using the notion of a model as applied in System Dynamics (SD) and Possible Worlds Semantics (PWS) as a starting point. I conclude by offering a generalization of the four concepts.